Digital literacy level and associated factors among health professionals in a referral and teaching hospital: An implication for future digital health systems implementation - Tegegne, Masresha Derese; Tilahun, Binyam; Mamuye, Adane; Kerie, Hailemariam; Nurhussien, Fedlu; Zemen, Endalkachew; Mebratu, Aragaw; Sisay, Girma; Getachew, Redet; Gebeyehu, Henok; Seyoum, Abiy; Tesfaye, Selamsew; et al. (Frontiers in Public Health, 2023)
Background In Ethiopia and other developing countries, electronic medical record systems and other health information technology are being introduced. However, a small proportion of low-income countries have successfully implemented national health information systems. One cause for this can be the lack of digital literacy among medical practitioners. As a result, this study aimed to assess health professionals’ digital literacy level and associated factors in Northwest Ethiopia. Method A quantitative cross-sectional study was employed among 423 health professionals working in a teaching and referral hospital in Northwest Ethiopia. We modified and applied the European commission’s framework for digital competency to assess the level of digital literacy among health professionals. We used stratified random sampling with proportional allocation to the size of the departments in the hospital to select study participants. Data were collected using a semi-structured, self-administered, and pretested questionnaire. Descriptive and binary logistic regression analysis techniques were used to describe respondents’ digital literacy level and identify its associated factor, respectively. The odds ratio with 95% CI and value of p were used to assess the strength of the association and statistical significance, respectively. Results Out of 411 participants, 51.8% (95% CI, 46.9–56.6%) of health professionals had adequate digital literacy. Holding a master’s degree (Adjusted OR = 2.13, 95% CI: 1.18–3.85), access to digital technology (AOR = 1.89, 95% CI: 1.12–3.17), having training in digital technology (AOR = 1.65, 95% CI: 1.05–2.59), and having a positive attitude towards digital health technology (AOR = 1.64, 95% CI: 1.02–2.68) were found to be significant factors associated with health professionals digital literacy level of health professionals. Conclusion Low level of digital literacy among health professionals was observed, with nearly half (48.2%) of them having poor digital literacy levels. Access to digital technology, training on digital technology, and attitude toward digital health technology were significant factors associated with digital literacy. It is suggested to increase computer accessibility, provide a training program on digital health technology, and promote a positive attitude toward this technology to improve the deployment of health information systems.